Goethe’s morphological method and its contribution in teaching and learning process - Ferraz, Maíra Kahl (Ciência e Natura, 2022)
Goethe’s morphological method is still little discussed in the sciences and education, despite its potential to contribute to such disciplines. From the observation of nature, Goethe developed his method based on the interaction between the subject and the object, in which observation and experience played a central role. The Goethian method proposed, then, other possibilities which were being established at the time, challenging a vision of mechanistic and utilitarian nature. These possibilities took effect until contemporary times. The mechanistic view of nature generated problems experienced in the scientific, economic, socio-cultural, environmental, and educational spheres. From this scope, this article aims to explain Goethe’s morphological method and point out its possible contributions to education. To this end, a bibliographic survey of the scientific works of Goethe and authors who dedicated themselves to understanding the Goethian method was carried out, in order to establish the guidelines of his method. Since Goethe’s method proposes changes in the way of experiencing phenomena and content, it can, in this way, assist in the educational process. Therefore, we understand that Goethe’s morphological method contributes to changes in the process of teaching and learning by proposing a participatory role for the subject in this discourse. The sessions in this article sought to develop such an understanding.